2021
DOI: 10.1038/s41598-021-89962-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of precipitation and temperature on maize production in the Czech Republic from 2002 to 2019

Abstract: Maize is one of the important food crops in the Czech Republic, its growth and productivity are influenced by climate change. This study investigated the influence of precipitation under recent climate change on maize yield both for grain and silage in the whole Czech Republic during 2002–2019. Total maize yield and yield rate increased in the Czech Republic from 1961 to 2010, but they became to decrease after 2010. This is in line with the tendency of decreased precipitation and an increase in temperature aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Organic farming represents an alternative to the classic intensive production and it is becoming more popular among the consumers as the environmental issues are more highlighted. However, it can be an alternative also for the producers, especially under the changing climate conditions [38,39]. This can be important for countries relying on agricultural production, where organic production can offer higher added value [40].…”
Section: Introductionmentioning
confidence: 99%
“…Organic farming represents an alternative to the classic intensive production and it is becoming more popular among the consumers as the environmental issues are more highlighted. However, it can be an alternative also for the producers, especially under the changing climate conditions [38,39]. This can be important for countries relying on agricultural production, where organic production can offer higher added value [40].…”
Section: Introductionmentioning
confidence: 99%
“…The fallow duration under winter wheat monoculture generally ranges from 3 months ( Wang et al, 2011 ) to 24 months ( Huang et al, 2015 ). Using the data for MAP instead of the precipitation occurred during fallow period or growing season may have led to some bias in this meta-analysis study, as wheat production is affected by not only SWSp but also water supply during growing season ( Brown and Rosenberg, 1997 ; Wang et al, 2011 ; Maitah et al, 2021 ). In Eastern United States, where the relationship between crop yield and precipitation revealed that moisture scarcity, however, herded crop yield ( Huang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, there are several works that show the relevance of these factors on maize yield in distinct parts of the world ( Table 1 ). Maitah et al (2021) , for example, demonstrated the influence of precipitation, from 2002 to 2019, on maize yield in the Czechia. They found that both total yield and yield rate increased from 1961 to 2010, but they dropped after 2010, just when precipitation also decreased.…”
Section: Effects Of Drought and Heat On Maize Crop Productivitymentioning
confidence: 99%
“…They found that both total yield and yield rate increased from 1961 to 2010, but they dropped after 2010, just when precipitation also decreased. After 2010, there was also a trend of increasing temperature that correlates with a decrease in total yield and yield rate ( Maitah et al, 2021 ). Data from more than 20,000 historical maize trials in Africa, from 1999 to 2007, combined with daily temperature and precipitation data, showed that each additional degree day above 30°C reduced the final yield by 1% under optimal rainfed conditions, and by 1.7% under drought ones ( Lobell et al, 2011 ).…”
Section: Effects Of Drought and Heat On Maize Crop Productivitymentioning
confidence: 99%